ChemInform Abstract: Metal‐Assisted Addition of a Nitrate Anion to Bis(oxy)enamines. A General Approach to the Synthesis of α‐Nitroxy‐oxime Derivatives from Nitronates. Issue 34 (4th August 2016) - Naumovich, Yana A.; Buckland, Victoria Emily; Sen'ko, Dmitry A.; Nelyubina, Yulia V.; Khoroshutina, Yulia A.; Sukhorukov, Alexey Yu.; Ioffe, Sema L.
Abstract: The method offers access to various cyclic and acyclic α‐nitroxy‐oxime derivatives which are obtained starting from bis(oxy)enamines which may be prepared in situ.